Extremism Counter-narration of the Jamaah Ansharut Daulah within the Perspective of Ludwig Wittgenstein Language Games Theory - Habibullah, Muhammad; Makinuddin, Muhammad (Nursyam Center, 2023)
Jamaah Ansharut Daulah (JAD) is one of the extreme Islamic groups that has a strong influence in the spread of takfiriism in Indonesia. This group has proven to be strongly affiliated with ISIS (Islamic State of Iraq and Syria), which is an extreme transnational Islamic group. JAD is one of the extreme groups in Indonesia that has the most followers and is spread throughout Indonesia. This is based on the large number of Indonesian people, especially Muslims who are exposed to JAD ideology. JAD has a different character from its predecessor group which also carried out acts of terrorism. JAD's character is like targeting a near enemy, disbelieving all those who serve the country, carrying out lone wolf actions, involving one family in its jihad, and involving women. Thus, this research leads to a form of counter-narrative/preventive effort as a form of self-defense to dispel such dangerous narratives. The study in this study uses a descriptive analysis model based on library research by taking data sourced from primary data, as well as secondary data. The findings in this study provide a new way of anticipating extreme narratives taught by JAD (Jamaah Ansharut Daulah), namely through the analysis of Ludwig Wittgenstein's language games. Through this analysis it can be found that there is a structure of propaganda language games, inciting, praying, and orders that are delivered religiously and in the form of justifications. Therefore, the analysis of language games provides a way, namely by paying attention to words according to their use in sentences, paying attention to the meaning of sentences according to their use in language, and paying attention to the meaning of language according to their use in life.